Unique Burdens of Pediatric Clinical Trials in Duchenne Muscular Dystrophy, April 20-21, 2017, Bethesda, Maryland, USA. (January 2019) - Franson, Timothy; Kinnett, Kathi; Cripe, Timothy P.
Recent increases in the number and breadth of clinical trials for patients with Duchenne muscular dystrophy (DMD) have engendered hope for a better future. Despite the overall enthusiasm by the DMD community for these trials, however, the burdens and pressures that they place on children with Duchenne muscular dystrophy and their families have become painfully apparent. In order to identify, and mediate, these challenges, Parent Project Muscular Dystrophy (PPMD) sponsored a meeting to examine some of these issues more closely in Bethesda, Maryland, on April 20-21, 2017. The meeting focused on key burdens for patients participating in clinical trials including technical (protocol complexity), financial, psychosocial and emotional issues, and informed consent. Participants recommended mitigation strategies falling into clinical, operations, regulatory, and ethical domains. The development of consensus action plans for short- and long-term enhancements in trials should facilitate discovery and development research for DMD patients.